O gênero textual dicionário no ensino de português como língua materna: uma proposta didática destinada a alunos de 8º ano - Cleide Aparecida Nunes Siqueira (2024)
ABSTRACT SIQUEIRA, Cleide Aparecida Nunes. The dictionary genre in the teaching of portuguese as a mother language: a didactic proposal for 8th grade students. Três Lagoas: Três Lagoas Campus of the Federal University of Mato Grosso do Sul. 2024. 73 f. (Professional Master's Dissertation in Letters) When developing activities in the practice of writing, text interpretation, reading and speaking, we observed the marked persistence of difficulties that 8th grade LP students in EF II still had and considering the linguistic skills desired by the normative and guiding documents of Brazilian education for the final grades of EF II (8th and 9th grades). We proposed, in this work, the continuous and systematic use of the dictionary as a textual genre as a teaching material that, linked to other genres, can greatly contribute to the acquisition, development and expansion of students' linguistic skills at this school stage, as long as it is consciously presented in its entirety by LP teachers as their mother tongue. We also discussed the importance of the school as, a mediator, to provide students with access to the most diverse textual genres existing in society as a means of expanding their linguistic skills. We consider the importance of Lexicography and Pedagogical Lexicography in the training of professionals in the field of Literature as a differential that can influence the methodology of these teachers with regard to teaching the lexicon. Finally, we suggest a Sequence of Activities (SA), based on the school dictionary, divided into two stages: the first part for the presentation of the macrostructure of the dictionary to 8th grade students and the second for the development of activities that aim to expand the learning of the Portuguese language in its orthographic, morphological and semantic forms. To this end, our specific objectives were: i) to discuss the importance of school in the acquisition and expansion of students' linguistic skills; ii) to discuss what is stated in official documents to in relation to linguistic skills that students need or should acquire in the final years of Elementary School, focusing on students in the 8th grade; iii) propose the use of the school dictionary as a textual genre in the 8th year of EF II, which, intertwined with other genres, can greatly contribute to the process of teaching and learning Portuguese as a mother tongue and in a school context; iv) emphasize the importance of Lexicography in the training of the Language and Literature professional; v) develop a SA structured in two stages, the first aimed at knowledge related to the dictionary as a textual genre and the second directed at activities that aim to develop linguistic competence in the basic skills that students need to develop during the process of acquiring and learning their mother tongue in the 8th year of EF II; vi) contribute with another support material to fellow Elementary School teachers in the final grades. Keywords: school dictionary; linguistic competence; sequence of activities.